Characterization and phylogenetic analysis of the complete mitochondrial genome from Rock Scallop (Crassadoma gigantea) using next-generation sequencing. Issue 2 (3rd July 2018) - Liao, Dejie; Zhou, Ying; Tong, Jingou; Cao, Shanmao; Yu, Xiaomu; Fu, Beide; Yang, Dazuo
Abstract: In this study, the complete 18, 495 bp mitochondrial genome was determined from Rock scallop ( Crassadoma gigantea ) using next-generation sequencing technology. The complete mitochondrial genome contained 12 protein-coding genes (PCGs), 2 ribosomal RNA genes, 23 transfer RNA genes, without ATP8 and D-loop, which was similar with most mitochondrial genomes of marine bivalve molluscs. Gene annotations, including gene order, genetic code, start and stop codons and codons bias, were identified. Phylogenetic tree was constructed using Neighbor-Joining (NJ) method based on the PCGs showed the present species clustered within the Pteriomorphia clade. This work should be of importance not only for the better understanding of the relationships within Pectinidae, but also for the development of useful genetic markers in Rock scallop aquaculture and restoration efforts.